The role of contactin-associated protein-like 2 in neurodevelopmental disease and human cerebral cortex evolution - St. George-Hyslop, Frances; Kivisild, Toomas; Livesey, Frederick J. (Frontiers in Molecular Neuroscience, 2022)
The contactin-associated protein-like 2 (CNTNAP2) gene is associated with multiple neurodevelopmental disorders, including autism spectrum disorder (ASD), intellectual disability (ID), and specific language impairment (SLI). Experimental work has shown that CNTNAP2 is important for neuronal development and synapse formation. There is also accumulating evidence for the differential use of CNTNAP2 in the human cerebral cortex compared with other primates. Here, we review the current literature on CNTNAP2, including what is known about its expression, disease associations, and molecular/cellular functions. We also review the evidence for its role in human brain evolution, such as the presence of eight human accelerated regions (HARs) within the introns of the gene. While progress has been made in understanding the function(s) of CNTNAP2, more work is needed to clarify the precise mechanisms through which CNTNAP2 acts. Such information will be crucial for developing effective treatments for CNTNAP2 patients. It may also shed light on the longstanding question of what makes us human.